1990
DOI: 10.1577/1548-8675(1990)010<0365:tiogoa>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Goals, Objectives, and Values in the Fisheries Management Process and Organization: A Review

Abstract: We review the managerial concepts of goals, objectives, and values, and their importance and function in fisheries management. Fishery management is a process aimed at accomplishing predetermined goals and objectives. Throughout the history of fisheries management, goals have been rarely stated explicitly or have been stated in generalized terms of "best" or "wise" use with no supporting objective statements. Goals are ideals, major accomplishments, ends, or states of affairs to be achieved. They direct a mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 20 publications
1
53
0
Order By: Relevance
“…Furthermore, effective communication skills are necessary to bring together a heterogeneous group of stakeholders and allow effective inland fisheries management (Brown 1996; Decker and Krueger 1999). Last but not the least, responsible (i.e., sustainable in the FAO Code of Conduct) management requires setting unambiguous and quantifiable objectives and management measures in cooperation with fishers, anglers and other interest groups (Lackey 1979; Barber and Taylor 1990; Cochrane 2000).…”
Section: Inland Fisheries and Sustainabilitymentioning
confidence: 99%
“…Furthermore, effective communication skills are necessary to bring together a heterogeneous group of stakeholders and allow effective inland fisheries management (Brown 1996; Decker and Krueger 1999). Last but not the least, responsible (i.e., sustainable in the FAO Code of Conduct) management requires setting unambiguous and quantifiable objectives and management measures in cooperation with fishers, anglers and other interest groups (Lackey 1979; Barber and Taylor 1990; Cochrane 2000).…”
Section: Inland Fisheries and Sustainabilitymentioning
confidence: 99%
“…As recreational fishing is important to some people and fish populations are tightly linked to fishers' actions, recreational fisheries management often jointly addresses human (fishers and non-fishers) well-being and conservation issues (Cowx et al 2010). One challenge of recreational fisheries management is to translate these vague management goals into operational objectives (Barber & Taylor 1990). Developing objectives for fisheries (resource) management requires answering normative questions about which dimensions of the system to focus on (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…While our model does recognize these capacity factors, an optimal angler‐day prediction greater than 90,000 is outside the range of our observed data. Another question is whether the optimal policy should focus on resident angler use as opposed to that by both resident and nonresident anglers (Barber and Taylor 1990). Such questions raise political and philosophical issues that should be evaluated with respect to overall program objectives and with input from fishery management administrators, game commissions, and the fishing public.…”
Section: Discussionmentioning
confidence: 99%
“…Tomlinson and Brown (1979) formulated principles for integrating management science and decision analysis in dealing with problems of hatchery development and management and raised the important question of what objective should be used for a recreational fish hatchery. Barber and Taylor (1990) concluded that effective fisheries management requires setting and meeting goals and objectives that serve the needs of both internal and external organizational environments. found that a goal must be set before a good fish stocking strategy can be designed, because no single stocking strategy is superior for all management goals.…”
Section: Introductionmentioning
confidence: 99%